Production and characterization of a bioflocculant from Aspergillus flavus and its applications in water treatment - Al Juboori, Ahmad H. Rajab (2012)
Flocculants are useful agents in the aggregating of colloids, cells and suspended solids. Various flocculants are commonly used in industrial fields. These flocculants can be classified into inorganic, organic synthetic and naturally occurring flocculants. The use of inorganic and organic synthetic flocculants has caused some environmental and health problems. For example, the aluminum element in polyaluminium chloride it could induce Alzheimer's disease and polyacrylamide derivatives contain acrylamide monomers which are both neurotoxic and carcinogens. In present study, the production and characterization of a bioflocculant named IH-7 by Aspergillus flavus was investigated to determine the optimal culture medium composition, environmental conditions, flocculation efficiency, flocculation mechanism and its application in water treatment. The highest production was obtained when sucrose and peptone with C/N ratio of 5/1 were used in production media with initial pH 7 and the cultivation was incubated for 60 hours at 40C. About 0.4 g of purified bioflocculant with average molecular weight of 2.574x104 Da, could be recovered from 1.0 L of fermentation broth. Chemical analysis showed that the purified IH-7 was mainly consisted of 28.5% protein and 69.7% polysaccharide. Fourier-transform infrared (FTIR) spectra indicated the presence of hydroxyl, amide, carboxyl and methoxyl groups in IH-7 molecules. The elemental analysis of purified IH-7 revealed that the weight fractions of the elements C, H, N, O and S were 29.9, 4.8, 3.3, 34.7 and 2.0%, respectively. The IH-7 bioflocculant showed good flocculation performance without cation addition. Thus, the study suggested charge neutralization is the flocculation mechanism of IH-7. The study found bioflocculant IH-7 is a cation-independent bioflocculant able to flocculate activated carbon, kaolin clay, soil solids and yeast cells without cations addition. Overall, the IH-7 flocculation performance was better than PAC at a wide range of flocculant concentrations, 0.5 mg/L of bioflocculant IH-7 was able to achieve more than 90% of flocculating efficiency, within pH range of 4 to 8 and initial kaolin concentrations range of 0.5 to 10 g/L. In addition, IH-7 was found to be a thermo-stable bioflocculant which has great potential to replace common chemical flocculants in cold weather countries, as well as in treating turbid water with salinity up to 10% w/w. The treatment of river water by IH-7 bioflocculant in comparison with Polyaluminium chloride (PAC) showed that purified IH-7 performed better than PAC and crude IH-7 in treating river water. Water with final turbidity 5 NTU, total solids 3.3 mg/L and Chemical Oxygen Demand 9.9 mg/L could be achieved when 4 mg/L of IH-7 was used to treat the river water. The use of IH-7 and PAC in discoloration of dye solutions for four types of dyes (Reactive Black 5, Methylene Blue, Fast Green and Crystal Violet), showed IH-7 bioflocculant and PAC were more effective to discolor the anionic dye solutions than cationic dye solutions. This study concluded, extracellular polymeric substance named IH-7 produced by Aspergillus flavus has excellent flocculation properties for many types of suspended solids at wide range of conditions. In addition, IH-7 performed better than synthetic chemical flocculant in surface water treatment and discoloration applications.